Use of low-cost adsorbent for waste water treatment: Recent progress, new trend and future perspectives - Mansoor Akhtar; Muhammad Sarfraz; Muhammad Ahmad; Nadeem Raza; Laiqi Zhang (Desalination and Water Treatment)
The development of highly effective and sustainable material production is necessary for the treatment of wastewater and the manufacture of clean water. The fate and transit of both organic and inorganic contaminants have drawn a lot of interest to waste biomass-derived adsorbent materials in environmental research and technology recently. Here, we present the process of turning different biomass wastes into useful adsorbent materials that may be used to clear contaminated water and solve the problem of their disposal. Consequently, the purpose of this review paper is to provide an overview of the most recent findings regarding the application of various waste biomass-derived materials for wastewater treatment. We have deep discussion on several activation techniques in the first section for using waste biomass as a highly effective, economical, and reusable material with a distinctive structure and properties. Second, a critical evaluation was conducted on the potential of various waste-derived adsorbent materials in addressing difficult environmental concerns, specifically in relation to the adsorption of contaminants such as metal ions, phenolic compounds, pharmaceuticals, and colors from contaminated water. Finally, we offered a succinct overview of the prospects, advancements, and outlook for the synthesis of affordable adsorbent materials produced from waste biomass for the treatment of wastewater in a sustainable manner.